Studying tree response to biotic stress using a multi-disciplinary approach: The pine pitch canker case study - Amaral, Joana; Valledor, Luis; Alves, Artur; Martín-García, Jorge; Pinto, Glória (Frontiers in Plant Science, 2022)
In an era of climate change and global trade, forests sustainability is endangered by several biotic threats. Pine pitch canker (PPC), caused by Fusarium circinatum, is one of the most important disease affecting conifers worldwide. To date, no effective control measures have been found for this disease. Earlier studies on PPC were mainly focused on the pathogen itself or on determining the levels of susceptibility of different hosts to F. circinatum infection. However, over the last years, plenty of information on the mechanisms that may explain the susceptibility or resistance to PPC has been published. This data are useful to better understand tree response to biotic stress and, most importantly, to aid the development of innovative and scientific-based disease control measures. This review gathers and discusses the main advances on PPC knowledge, especially focusing on multi-disciplinary studies investigating the response of pines with different levels of susceptibility to PPC upon infection. After an overview of the general knowledge of the disease, the importance of integrating information from physiological and Omics studies to unveil the mechanisms behind PPC susceptibility/resistance and to develop control strategies is explored. An extensive review of the main host responses to PPC was performed, including changes in water relations, signalling (ROS and hormones), primary metabolism, and defence (resin, phenolics, and PR proteins). A general picture of pine response to PPC is suggested according to the host susceptibility level and the next steps and gaps on PPC research are pointed out.